Simvastatin's Application in dentistry. A narrative review. (Mustansiria Dental Journal, 2025)
Simvastatin a pharmaceutical drug, belongs to the statin’s family, that shares the same properties of their mechanism of action which is summarized by the lowering of hypercholesteremia, by averting the production of mevalonate from HMG-CoA which is a compulsory product in the cholesterol synthesis pathway. Th proved effect of oral administration of Simvastatin on increasing of bone formation and reduction of bone resorption by over expression of BMP-2 and lowering the bone resorption markers abetted by its safe use and feasibility made it an interest point of many researchers. Various dental studies have shown a positive response to both oral and local administration of statins concerning periodontal health, including a notable decrease in tooth mobility, improved clinical attachment levels, and enhanced bone fill in cases of type II diabetes having chronic periodontitis. Researchers propose that simvastatin may partially mitigate the frequency and severity of relapse, while others indicate that exosome-based drug delivery holds considerable promise for therapeutic applications in orthodontics. Furthermore, simvastatin exhibits diverse effects and applications across various fields of dentistry. The aim of this review is to entails the benefits and applications of statins in many domains of dentistry including original manuscripts for the last five years.